Effects of different rootstocks on aroma volatile constituents in the fruits of peach (Prunus persica L. Batsch cv. ‘Cresthaven’) - Şeker, Murat; Gür, Engin; Ekinci, Neslihan (NEW ZEALAND JOURNAL OF CROP AND HORTICULTURAL SCIENCE, 2017)
The consumption of peaches is dependent on fruit quality. Aromatic compounds directly affect the sensorial quality and consumer acceptance of peaches. This study evaluated the fruit quality and aroma volatile constituents of the peach cultivar Cresthaven' grafted on to five different rootstocks in 2012 and 2013. The rootstocks used were Uzunoglu Seedling' (Prunus persica), GF677' (P. persicaxP. dulcis), Nemaguard' (P. persicaxP. davidiana), Cadaman' (P. persicaxP. davidiana) and St. Julien GF 655/2' (P. insititia). Fruits were sampled at the commercial maturity stage around mid-August. Fruit quality characteristics and aroma volatiles differed significantly in peaches grown on different rootstocks. The largest fruits and highest titratable acidity were obtained from Cadaman'. The major volatile constituents of Cresthaven' fruits were acetaldehyde, hexanal, benzaldehyde, ethanol, 1-hexanol, (Z)-3-hexenol, (E)-2-hexen-1-ol, linalool, ethyl acetate, hexyl acetate, (Z)-3-hexenyl acetate, (E)-2-hexenyl acetate, 6-methyl-5-hepten-2-one, (E)--ionone, -decalactone and limonene. The type and concentration of volatile compounds showed great variability in Cresthaven' peach grafted on to different rootstocks. A total of 91 volatile compounds were detected and the highest volatile content was found in GF677'.
Keywords: Aldehyde; Aroma; Ester; Fruit Quality; GC-MS; HS-SPME; Lactone